Ensuring supplies of medicines during pandemics in terms of public procurement - Vlček, Vít (Central European Journal of Public Health, 2018)
OBJECTIVES: This article describes and comments on contemporary legal regulations concerning the supply of medicines during pandemics in terms of public procurement. METHODS: Suggestions are made for removing existing legislative shortcomings, clarifying the diction of existing laws or rendering precision to legal regulation of public procurement given purchases of medicines during periods of imminent threats of pandemics and duration of pandemics. RESULTS: The author reflects on improving legislation concerning the lack of clarity and the doubts concerning the contemporary legal order of the Czech Republic, with reference to speeding up and simplifying public procurement procedures for incident-free purchases of necessary medicines in time of pandemic crisis situation and then effectively supporting the struggle against any pandemic infection. CONCLUSION: The issues raised should be addressed since better legislation can significantly contribute to the containment of pandemics and their consequences for individual and public health.
Keywords: veřejné zdravotnictví; zdravotnické prostředky; Česká republika; Humans; lidé; pandemie; Public Health; Pandemics; Czech Republic; Equipment and Supplies